IMF Research Bulletin, December 2012. (IMF Research Bulletin; IMF Research Bulletin ;, 2012)
The Research Summaries in the December 2012 IMF Research Bulletin look at "Market Failures and Macroprudential Policy" (Giovanni Favara and Lev Ratnovski) and "Measurement Matters for House Price Indices" (Mick Silver). The Q and A column looks at "Seven Questions on Turning Points of the Global Business Cycle." The Bulletin also includes a listing of recent IMF Working Papers and Staff Discussion Notes, as well as a list of the top-viewed articles for the first three issues of IMF Economic Review in 2012. Information is also included on a call for papers for the conference "Asia: Challenges of Stability and Growth" to be held in Seoul in 2013.